Religious and Socio-Cultural Affinities: The Role of Shared Heritage in India-Nepal Relations. - U Din Mir., Mehraj (International Journal of Psychosocial Rehabilitation, 2019)
This research paper examines the impact of shared religious and socio-cultural heritage on the diplomatic relations between India and Nepal. Through an exploration of historical ties, religious practices, cultural exchanges, and peopleto-people connections, the study highlights the profound influence of these affinities. The research underscores how these shared elements serve as bridges that transcend political boundaries, fostering mutual understanding, soft power diplomacy, and collaborative initiatives. While celebrating the positive role of shared heritage, the paper also addresses challenges and sensitivities that arise. Ultimately, the study emphasizes the enduring significance of these ties in shaping the interactions between these neighboring countries.